Analysis of Taiwan’s transport system - Chabreček, Lukáš (2020)
This master’s thesis deals with the transport system of Taiwan, the Republic of China. The main objective is to analyze the transport system of the country and to describe the various modes of transport with the development of these modes in recent years with a forecast for the future. The theoretical part defines the historical development of individual modes of transport with its subsequent characteristics, among which the author lists air, water, rail and road transport. The analytical part introduces the reader to the geographical characteristics of Taiwan with emphasis on the importance of the physical geography of the country, which affects the development of its transport system. Subsequently, the economic and social importance of individual modes of transport are analyzed in detail. Moreover, sector of personal transport and integrated transport systems that are used in the country are also characterized. In the analysis of personal transport, author focuses on a detailed analysis in the capital city, Taipei. The analytical part is enriched with a SWOT matrix and suggestions for improvement of the transport system. The benefit of this thesis is to get acquainted with the transport system of Taiwan and its history for an easier orientation in it for future visitors of the country.